Characterisation of the cellulolytic and hemicellulolytic system of Bacillus Licheniformis SVD1 and the isolation and characterisation of a multi-enzyme complex - Van Dyk, Jacoba Susanna (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
The biological degradation of lignocellulose into fermentable sugars for the production of liquid transportation fuels is feasible and sustainable, but equires a variety of enzymes working in synergy as lignocellulose is a complex and recalcitrant substrate. The cellulosome is a multi-enzyme complex (MEC) with a variety of cellulolytic and hemicellulolytic enzymes that appears to facilitate an enhanced synergy and efficiency, as compared to free enzymes, for the degradation of recalcitrant substrates such as lignocellulose and plant cell walls. Most of the studies on cellulosomes have focused on a few organisms; C. thermocellum, C. cellulovorans and C. cellulolyticum, and there is only limited knowledge vailable on similar complexes in other organisms. Some MECs have been identified in aerobic bacteria such as Bacillus circulans and Paenibacillus curdlanolyticus, but the nature of these MECs have not been fully elucidated. This study investigated the cellulolytic and emi-cellulolytic system of Bacillus licheniformis SVD1 with specific reference to the presence of a MEC, which has never been reported in the literature for B. licheniformis. A MEC of approximately 2,000 kDa in size, based on size exclusion chromatography using Sepharose 4B, was purified from a culture of B. licheniformis. When investigating the presence of enzyme activity in the total crude fraction as well as the MEC of a birchwood xylan culture, B. licheniformis was found to display a variety of enzyme activities on a range of substrates, although xylanases were by far the predominant enzyme activity present in both the crude and MEC fractions. Based on zymogram analysis there were three CMCases, seven xylanases, three mannanases and two pectinases in the crude fraction, while the MEC had two CMCases, seven xylanases, two mannanases and one pectinase. The pectinases in the crude could be identified as a pectin methyl esterase and a lyase, while the methyl esterase was absent in the MEC. Seventeen protein species could be detected in the MEC but only nine of these displayed activity on the substrates tested. The possible presence of a Î²-xylosidase in the crude fraction was deduced from thin layer chromatography (TLC) which demonstrated the production of xylose by the crude fraction. It was furthermore established that B. licheniformis SVD1 was able to regulate levels of enzyme expression based on the substrate the organism was cultured on. It was found that complexed xylanase activity had a pH optimum of between pH 6.0 and 7.0 and a temperature optimum of 55oC. Complexed xylanase activity was found to be slightly inhibited by CaCl2 and inhibited to a greater extent by EDTA. Complexed xylanase activity was further shown to be activated in the presence of xylose and xylobiose, both compounds which are products of enzymatic degradation. Ethanol was found to inhibit complexed xylanase activity. The kinetic parameters for complexed xylanase activity were measured and the Km value was calculated as 2.84 mg/ml while the maximal velocity (Vmax) was calculated as 0.146 U (Î¼mol/min/ml). Binding studies, transmission electron microscopy (TEM) and a bioinformatic analysis was conducted to investigate whether the MEC in B. licheniformis SVD1 was a putative cellulosome. The MEC was found to be unable to bind to Avicel, but was able to bind to insoluble birchwood xylan, indicating the absence of a CBM3a domain common to cellulosomal scaffoldin proteins. TEM micrographs revealed the presence of cell surface structures on cells of B. licheniformis SVD1 cultured on cellobiose and birchwood xylan. However, it could not be established whether these cell surface structures could be ascribed to the presence of the MECs on the cell surface. Bioinformatic analysis was conducted on the available genome sequence of a different strain of B. licheniformis, namely DSM 13 and ATCC 14580. No sequence homology was found with cohesin and dockerin sequences from various cellulosomal species, indicating that these strains most likely do not encode for a cellulosome. This study described and characterised a MEC that was a functional enzyme complex and did not appear to be a mere aggregation of proteins. It displayed a variety of hemi-cellulolytic activities and the available evidence suggests that it is not a cellulosome, but should rather be termed a xylanosome. Further investigation should be carried out to determine the structural basis of this MEC.
Keywords: Lignocellulose; Lignocellulose -- Biotechnology; Lignocellulose -- Biodegradation; Plant biotechnology